Analysis of water-filling process in goaf of closed mine - BI Yaoshan; WU Jiwen; WANG Guangtao; ZHAI Xiaorong; ZHANG Hongmei; HUANG Kai (Gong-kuang zidonghua, 2018)
In order to research water-filling problem in goaf of closed mine, taking Daihe Coal Mine as research object， mining space method was used to calculate water-filling volume in goaf of the closed mine according to geological and hydrogeological conditions of the coal mine as well as exploration and drainage data of previous working face goaf, and water-filling process in goaf of the closed mine was analyzed. The analysis results are as follows: ① Total water-filling volume in goaf after Daihe Coal Mine being closed is 6 208 267.20 m3, which includes 4 808 923.58 m3 in working face goaf and 1 399 343.62 m3 in abandoned roadways. If water bursting speed is 80 m3/h, then the closed coal mine will fully filled with water after 3 233.47 days. ② Relationship expressionbetween water-filling height (H) and time (td) is H=2×10-8t3d-7×10-5t2d+0.131 7td-415.29.